2018
DOI: 10.1111/evj.12963
|View full text |Cite
|
Sign up to set email alerts
|

Association between hyperinsulinaemia and laminitis severity at the time of pituitarypars intermediadysfunction diagnosis

Abstract: Although radiographic abnormalities were present in most animals at the time of PPID diagnosis, chronic laminitis remained unrecognised by many owners. Owner awareness of laminitis increased with severity of hyperinsulinaemia and higher insulin concentrations were detected in association with more severe radiographic changes. The Summary is available in Chinese - See Supporting Information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 38 publications
1
57
0
1
Order By: Relevance
“…Clinicians should also endeavor to educate horse/pony owners about the requirement for timely intervention for an animal with laminitis that might be in considerable pain, given the concerning finding from the current study that just over 50% of cases waited >10 days for veterinary attention. Recent reports that owners might fail to recognize laminitis in its early or mild stages is supportive of this perception . However, it is also possible that farriery assistance was sought before veterinary intervention in some cases in the current study.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Clinicians should also endeavor to educate horse/pony owners about the requirement for timely intervention for an animal with laminitis that might be in considerable pain, given the concerning finding from the current study that just over 50% of cases waited >10 days for veterinary attention. Recent reports that owners might fail to recognize laminitis in its early or mild stages is supportive of this perception . However, it is also possible that farriery assistance was sought before veterinary intervention in some cases in the current study.…”
Section: Discussionmentioning
confidence: 52%
“…The median insulin concentration was higher (P < .02) in animals with both equine metabolic syndrome (EMS) and pituitary pars intermedia dysfunction (PPID), compared to animals with EMS, PPID, or a pasture-associated cause of the disease (A). The insulin concentration was negatively correlated with height at the withers in the cohort (B); however, the insulin concentration did not differ among the seasons (C) 8.5 [3][4][5][6][7][8][9][10][11]…”
Section: Descriptive Epidemiology: Laminitismentioning
confidence: 99%
See 1 more Smart Citation
“…Laminitis is an acute disease, with the early subclinical phase usually undetectable . Furthermore, horse owners might not be particularly skilled at identifying the disease . Another recent study examining this same cohort of animals also found that owners frequently did not call the veterinarian until later in the clinical time course of the disease .…”
Section: Discussionmentioning
confidence: 99%
“…The critical factor in cases of endocrinopathic laminitis appears to be insulin dysregulation (ID), which results from a complex, often multifactorial disruption to the normal interactions between glucose and insulin. The diagnosis and management of ID can be challenging, and failure to recognize and control the underlying endocrinopathy means that laminitis might recur and become chronic . Furthermore, the management of ID currently relies on ongoing strategies to mitigate hyperinsulinemia, such as dietary restriction, weight loss, and exercise, the success of which is dependent on owner compliance …”
Section: Introductionmentioning
confidence: 99%